A life–threatening small bowel obstruction as onset of an unknown sarcoidosis: A case report. (2021) - Paone, Gregorino; Steffanina, Alessia; De Rose, Giulia; Leonardo, Giacomo; Colombo, Daniele; Ricci, Paolo; Sabetta, Francesco; Vaccaro, Francesco; Rosato, Edoardo; Palange, Paolo
Abstract: Sarcoidosis is a systemic granulomatous disorder of unknown etiology characterized by non-caseating granulomas at the site of disease. A confident diagnosis should be established by the evidence of typical granulomas on biopsy and after exclusion of other conditions. Clinically recognizable Gastrointestinal involvement (GI) occurs in less than 1.6% of patients with sarcoidosis, with data revealing small intestine participation in 0.03% of the cases and few anecdotal reports describe a peritoneal presentation. Clinical manifestations of peritoneal sarcoidosis are abdominal discomfort, bloating, weight loss, epigastric and peri-umbilical pain with or without ascites, bowel obstruction. Treatment depends on symptoms and disease activity. Herein we describe the case of a 42-years-old male patient who developed an acute, life–threatening small bowel obstruction as first manifestation of sarcoidosis. To the best of our knowledge, this is the only report showing such extensive and acute onset of intra-abdominal sarcoidosis in the absence of a previous disease manifestation and without pulmonary involvement. Highlights: Abdominal sarcoidosis is a sporadic event and localization without pulmonary involvement is rarer mimicking GI diseases. Reaching abdominal sarcoidosis diagnosis is not a straightforward process. It is pivotal to confirm sarcoidosis diagnosis before subjecting patients to an appropriate treatment. Corticosteroids are considered the cornerstone treatment. Asymptomatic patients may undergo a watch and wait follow-up with no need for a pharmacological therapy. Surgery is not often required but individualized patient evaluation is recommended.